A política de assistência técnica de extensão rural no Maranhão: do desmonte a (re) estruturação da política nos anos 2000 - Furtado, Carlos Augusto de Oliveira (2018)
Several studies on technical assistance and rural extension have sought to address the issue by focusing on the educational character of the extensionist, the extensionist - smallholder relationship, the extensionist practice and its ideological character, as well as its role within the capitalist system. In this work the focus was the analysis of the Policy of Technical Assistance and Rural Extension in Maranhão, as an agricultural policy instrument as a form of State intervention in Agriculture, through its evolution / involution, following the ongoing development process in the country and in the Maranhão in the proposed period; rescuing the role of conservative modernization for smallholder farmers; characterizing agriculture in Maranhão and the small rura l producer in the area group up to 100ha, until we reached the ATER Policy, with its structuring, restructuring and reorganization of Politics in Brazil and Maranhão. The analysis begins in 1985 and runs through 2006, when the state government finally creates the AGERP. The study showed that even before the so-called "dismantling / dismantling" phase of the ATER Policy in Maranhão, rulers no longer prioritized the small rural producer, offering the services of ATER, fact verified by the statistics of the number of establishments served. In the period under study, the governors prioritized modernization of large industrial projects (based on the exploration and production of iron, steel, cellulose and aluminum, structuring the insertion and expansion of agribusiness), placing Maranhao on the transnational capital route. The analysis developed here, highlighting the role of the smallholder in Maranhão agriculture, leads us to reflect on the importance of this segment as agents of agricultural development, given its participation in GDP even with the low technological index, still producing food, with ability to create jobs, generate income, and are systematically excluded from development policies. The option between making the ATER Policy publicly financed with funds from the Maranhão Treasury for the small rural producer or including the state on the international capital route is proof that the State assumes the social costs resulting from the second option